Approaches to improve the film ductility of colorless cycloaliphatic polyimides. (28th November 2017) - Hasegawa, Masatoshi; Fujii, Mari; Wada, Yuriko
Abstract : This study described approaches for improving the film ductility of colorless cycloaliphatic polyimides (PIs). An unexpected toughening effect was observed when a PI derived from pyromellitic dianhydride (PMDA) and 4, 4′‐methylenebis(cyclohexylamine) was modified by copolymerization with a low isophoronediamine (IPDA) content of 5 to 30 mol%, despite there being no film‐forming ability in the homo PMDA/IPDA system. For example, at an IPDA content of 20 mol%, the copolymer showed significantly improved film toughness (maximum elongation at break, ε b max = 57%), excellent optical transparency (light transmittance at 400 nm, T 400 = 83.7%), and a high glass transition temperature ( T g = 317°C). This toughening effect can be interpreted on the basis of the concept of chain slippage. In this study, the PIs derived from bicyclo[2.2.2]octane‐2, 3, 5, 6‐tetracarboxylic dianhydride (H‐BTA) with various diamines were also systematically investigated to evaluate the potential of H‐BTA‐derived systems. The combinations of H‐BTA with ether‐containing diamines led to highly tough PI films ( ε b max > 100%) with very high T g s, strongly contrasting with the results of an earlier study. The observed excellent properties are related to the steric structure of H‐BTA. Our interest also extended to the solution processability. A copolyimide derived from H‐BTA with a sulfone‐containing diamine and an ether‐containing diamine achieved a very high optical transparency ( T 400 = 86.8%), a very high T g (313°C), and good ductility ( ε b max = 51%) while maintaining solution processability. Thus, these approaches enabled us to dramatically improve the ductility of cycloaliphatic PI films that have, to date, been considered brittle.